Mass spectrometry for the novice - Greaves, John; Roboz, John, 1931- (Boca Raton, FL : Taylor and Francis, 2014)
"Mass Spectrometry has grown immeasurably over the last twenty years. It may well be the technique to turn to if you want to analyze gases, pharmaceuticals, drugs of abuse, environmental pollutants, search for explosives at airports, to sequence peptides from proteins or understand the role of complex carbohydrates in cancer. There are an ever-increasing number of scientists coming into contact with the technique"--
Incluye un disco compacto: Mass spectrometry for the novice. ISBN 9781420094183
Keywords: ESPECTROMETRIA DE MASAS